Hydro-climatic variations, changes, and extremes in the Baltic Sea Drainage Basin - Destouni, Georgia; Zarei, Mohanna (Frontiers in Environmental Science, 2025)
It is largely unknown, yet essential for the Baltic Sea state, the nutrient and pollutant loads from land, and the coastal-marine ecosystem health how freshwater discharges to the sea and their drought and flood extremes vary and change over the Baltic Sea Drainage Basin (BSDB). Based on four different (types of) datasets, we here compare these variations and changes over 1980-2010 across 69 large hydrological catchments in the BSDB. The datasets agree that the precipitation changes over the study period do not necessarily propagate to analogous changes for runoff and related discharges to the sea, with results showing various contrasting precipitation and runoff changes. The datasets differ markedly in that some model-based reanalysis datasets yield directly opposite water balance closures, implying persistent 30-year average regional storage wetting or drying depending on the dataset. For droughts and floods, dataset differences are overall greater for runoff than for precipitation, and widely used reanalysis data do not fully capture how extremely high and low flood- and drought-related runoff fluxes can be, as observed in the BSDB. These findings are important for plans and preparations to mitigate and/or adapt to changes and extremes in the Baltic freshwater conditions and discharges to the sea.